ANALISIS PERBEDAAN PENDAPATAN GOJEK SEBELUM DAN SESUDAH PANDEMI COVID-19 - Nida Putri Rahmayanti; Anthonius J Karsudjono (Media Mahardhika, 2023)
This study's objective is to examine the differences in Gojek's income before and after Covid 19. Because this transportation is very important in the economy of a region. In research with this type of quantitative research, namely distributing questionnaires to Gojeks in Banjarmasin City. Total population of 300 people with 123 samples of respondents who returned the questionnaire and completely answered the questionnaire. The following are the results of the research: the hypothesis is accepted, there is a difference in Gojek's income between before and after Covid-19. The reason is because there are many factors such as rules or policies from the government that require an area to be locked down, then several companies are laying off their employees.